The Effectiveness of Ultrasound Guidance in Pediatric Surgery a Prospective Interventional Study - Muhammad Younas Khan, Muhammad Javed Khan, Fayaz Iqbal, Wardah Saleem, Muhmmand Shoaib, Kifayat, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives 1 To investigate the effectiveness of ultrasound guidance in pediatric surgical procedures. 2 To compare the surgery duration and success rate between the group with ultrasound guidance and those without it. 3 To assess the potential complications associated with ultrasound guidance for pediatric surgery. 4 To discuss the importance of ultrasound guidance in pediatric surgical procedures. Methods: This prospective interventional study was conducted in the Department of Pediatric Surgery, Lady Reading Hospital (LRH), Peshawar, Pakistan, from January 2021 to January 2022. The study's sample size included sixty patients between the ages of one to fifteen years, who were divided into two groups of thirty. In the first group, the patients underwent an ultrasound examination before the surgical procedure, while in the second group, the patients did not undergo an ultrasound examination. After the surgical procedure, the duration of surgery was recorded and observed for comparison between the two groups. The success rate of the course was also honoured concerning each group. Statistical analysis was done by SPSS version 22.0, and the P-value was set to < 0.05 for the significance test. Results: The study results reveal that ultrasound guidance was significantly practical (p-value < 0.05) in reducing the surgery duration by an average of 10 minutes compared to the group without ultrasound guidance. Moreover, the procedure's success rate was also significantly improved (p-value < 0.001) in the ultrasound-guided group, with no significant complications. Conclusion: The present study concluded that ultrasound guidance effectively reduces the surgery duration and improves the success rate of pediatric surgical procedures. The study also highlighted the importance of this advanced imaging technique in pediatric surgery. The study recommends that ultrasound guidance be used routinely for pediatric surgeries to obtain accurate results and minimize potential risks. Keywords: Ultrasound Guidance, Pediatric Surgery, Surgery Duration, Success Rate, Complications.